Reassessing the Productivity Gains from Trade Liberalization - Ahn, JaeBin (IMF Working Papers; Working Paper ;, 2016)
This paper reassesses the impact of trade liberalization on productivity. We build a new, unique database of effective tariff rates at the country-industry level for a broad range of countries over the past two decades. We then explore both the direct effect of liberalization in the sector considered, as well as its indirect impact in downstream industries via input linkages. Our findings point to a dominant role of the indirect input market channel in fostering productivity gains. A 1 percentage point decline in input tariffs is estimated to increase total factor productivity by about 2 percent in the sector considered. For advanced economies, the implied potential productivity gains from fully eliminating remaining tariffs are estimated at around 1 percent, on average, which do not factor in the presumably larger gains from removing existing non-tariff barriers. Finally, we find strong evidence of complementarities between trade and FDI liberalization in boosting productivity. This calls for a broad liberalization agenda that cuts across different areas.